miR-615 facilitates porcine epidemic diarrhea virus replication by targeting IRAK1 to inhibit type III interferon expression - Zheng, Hong-qing; Li, Cheng; Zhu, Xiao-fu; Wang, Wei-Xiao; Yin, Bao-ying; Zhang, Wen-juan; Feng, Shu-lin; Yin, Xun-hui; Huang, He; Zhang, Yan-ming (Frontiers in Microbiology, 2022)
Porcine epidemic diarrhea virus (PEDV) is a highly contagious enteric Coronavirus in the swine industry and has evolved mechanisms to evade host innate immune responses. The PEDV-mediated inhibition of interferons (IFNs) has been linked to the nuclear factor kappa B (NF-κB) pathway. microRNAs (miRNAs) are involved in virus–host interactions and IFN-I regulation. However, the mechanism by which nucleic acid level regulates IFN during PEDV infection has not yet been investigated in its natural target cells. We report a novel mechanism of miRNA (miR-615) screened from high-throughput sequencing in porcine intestinal epithelial cells (IECs) infected with PEDV. PEDV infection altered the profiles of miRNA and activities of several pathways involved in innate immunity. Overexpression of miR-615 increased PEDV replication, inhibited IFNs expression, downregulated the NF-κB pathway, and blocked p65 nuclear translocation. In contrast, knockdown of miR-615 enhanced IFNs expression, suppressed PEDV replication, and activated the NF-κB pathway. We further determined that IRAK1 is the target gene of miR-615 in IECs. Our findings show that miR-615 suppresses the activation of the NF-κB pathway by suppressing the IRAK1 protein and reducing the generation of IFN-IIIs, which in turn facilitate PEDV infection in IECs. Moreover, miR-615 inhibited PEDV replication and NF-κB pathway activation in both IEC and MARC-145 cells. These findings support an important role for miR-615 in the innate immune regulation of PEDV infections and provide a novel perspective for developing new treatments.